Subsurface drip irrigation for alfalfa in Kansas - Alam, Mahbub, author; Trooien, Todd, author; Stone, Steven, author; Rogers, Danny, author (Colorado State University. Libraries, 2001)
The result from a two year field study on suitability of using subsurface drip irrigation (SDI) for Alfalfa provided some answers to alfalfa producers of Kansas. The study was set-up in a producer field for demonstration. The soil belongs to Otero-Ulysses complex and sandy loam in texture. The treatments included placement of drip tapes at (a) 1.5 M spacing at 0.46 and 0.30 M depth of placement, (b) 1.0 M spacing at 0.46 and 0.30 M depth, (c) 0.76 M spacing at 0.46 depth, and (d) a center pivot sprinkler irrigated plot seeded to alfalfa. Emergence of seedlings was adversely affected at 1.5 M spacing of drip tapes showing 'striping'. The total yield was reduced for spacing of drip tapes at 1.5 M in both 1999 and 2000. The depth of placement of the drip tapes (0.46 and 0.30 meters) showed no effect on yields.
Not digitized by CSUL Digital Services.
Presented at the Central Plains irrigation short course and exposition on February 5-6, 2001 at the Holiday Inn in Kearney, Nebraska.